Pengaruh Persepsi Harga, Promosi Online Dan Keragaman Produk Terhadap Keputusan Pembelian Konsumen Di Aulia Fashion Tasikmalaya (Survei Pada Konsumen Aulia Fashion Kabupaten Tasikmalaya) - Ai Yuni Sobi Baturohmah; Suci Putri Lestari; Nita Fauziah Oktaviani (Jurnal Ekonomi dan Bisnis Digital, 2024)
This research aims to analyze how price perceptions, online promotions and product diversity, both simultaneously and partially, can influence purchasing decisions at Aulia Fashion Tasikmalaya. The method used is a quantitative method with a survey approach. The sampling technique uses the Nonprobability Sampling technique with the Purprosive Sampling method, the number of samples used is 100 respondents with the criteria being Aulia Fashion consumers who live in Tasikmalaya and have made purchases at Aulia Fashion Tasikmalaya. The analytical tool used is multiple linear regression with SPSS Version 25 software tools. The research results show that price perceptions, online promotions and product diversity can simultaneously influence purchasing decisions at Aulia Fashion Tasikmalaya significantly, with a large influence. Price perceptions partially have no significant effect on purchasing decisions at Aulia Fashion Tasikmalaya, while online promotions and product diversity partially have a significant effect on purchasing decisions at Aulia Fashion Tasikmalaya.